Pilot survey of oral health-related quality of life: a cross-sectional study of adults in Benin City, Edo State, Nigeria - Lugo R Iván; Chattopadhyay Amit; Okunseri Christopher; McGrath Colman (BMC, 2005)
Abstract Background Oral health studies conducted so far in Nigeria have documented prevalence and incidence of dental disease using traditional clinical measures. However none have investigated the use of an oral health-related quality of life (OHRQoL) instrument to document oral health outcomes. The aims of this study are: to describe how oral health affects and impacts quality of life (QoL) and to explore the association between these affects and the oral health care seeking behavior of adults in Benin City, Edo State, Nigeria. Methods A cross-sectional survey recruited 356 adults aged 18-64 years from two large hospital outpatient departments and from members of a university community. Closed-ended oral health questionnaire with "effect and impact" item-questions from OHQoL-UK© instrument was administered by trained interviewers. Collected data included sociodemographic, dental visits, and effects and impact of oral health on QoL. Univariate and bivariable analyses were done and a chi-square test was used to test differences in proportions. Multivariable analyses using ANOVA examined the association between QoL factors and visits to a dentist. Results Complete data was available for 83% of the participants. About 62% of participants perceived their oral health as affecting their QoL. Overall, 82%, 63%, and 77% of participants perceived that oral health has an effect on their eating or enjoyment of food, sleep or ability to relax, and smiling or laughing, respectively. Some 46%, 36%, and 25% of participants reported that oral health impact their daily activities, social activities, and talking to people, respectively. Dental visits within the last year was significantly associated with eating, speech, and finance (P < 0.05). The summary score for the oral health effects on QoL ranged from 33 to 80 with a median value of 61 (95% CI: 60, 62) and interquartile range of 52-70. Multivariable modeling suggested a model containing only education (F = 6.5, pr>F = 0.0111). The mean of effects sum score for those with secondary/tertiary education levels (mean = 61.8; 95% CI: 60.6, 62.9) was significantly higher than those with less than secondary level of education (mean = 57.2; 95% CI: 57.2, 60.6). Conclusion Most adults in the study reported that oral health affects their life quality, and have little/no impact on their quality of life. Dental visits within the last year were associated with eating, speech, and finance.